ASSOCIATION REPORTS. - Miller, Hermann C.; Chizek, C. F. (The Accounting Review, 1948)
Abstract The article reports on the achievements and progress of the American Accounting Association. One of the impressive accomplishments of the association was the marked increase in membership. The widespread interest of professional practitioners in the work, the aims and objectives, the publications, and the activities of the association in the held of accounting education has been gratifying. Many new teachers at the college level have been added to the membership roles. To all of these new members the association extends a warm and cordial welcome and a standing invitation to participate actively in furthering the purposes which are set forth in our by-laws and statement of purposes. The program of the annual meeting gave a glimpse into still another new undertaking, namely, the development of standards rating in the field of undergraduate and graduate study of accounting. It is hoped that extension of this project may become a continuing activity of the association.